Routing of Periodicals to Managers: Some Behavioural Aspects and Guidelines - Pratap Lingam, P. (Journal of Information and Knowledge, 1983)
This Paper points out me significance of service of Routing of Periodicals, presents a Study conducted on behavioural aspects of such service to the managers in a textile industry and its findings, briefly describes the activities which should constitute a ’routing procedure’, analyses and discusses the existing routing procedures and solutions to the problems faced in (a) deciding the sequence of users on the ’routing slips’ which have direct impact on behavioural aspects of users and procedures, and (b) in formulating guidelines helpful both in evolving and successfully implementing a routing procedure acceptable to majority of users in any industry or organisation.